HUBUNGAN MOTIVASI BELAJAR DENGAN KECEMASAN MAHASISWA MENGHADAPI OSCE - Lilis Novitarum; Lindawati Farida Tampubolon; Rina Amorita Manurung (Jurnal Ilmiah Keperawatan, 2018)
Anxiety is a feeling of anxious, worried, discomfort or fear. Anxiety often occurs in students facing exams test mainly the OSCE, the anxiety may be reduced if students can master the lessons that followed. Factors that can be affected the activity of a person is motivated to learn, where the motivation is symptom that arise within and from outside themselves that pushing to do something to achieve the expected goal and motivation is also the basis mover pushing to learn.. The purposed of this study was to identify the correlation between learning motivation and the anxiety of the sixth semester college students of Ners which follow the OSCE examination. Kind of this study was descriptive correlation that use the cross sectional approach. Population of this study is all student sixth semester of ners is 61 reponden. Sampling has done by using total sampling technique. The result of statistic test Spearman Rank shows that There was a correlation the motivation to study with anxiety students for following OSCE (p value=0,038), but the power of this relationship is still weak ( r = 0,266 ) because there are other factors that could affect the anxiety when take OSCE examination